0.4 J/10 ns/10 kHz‐4 kW coherent beam combined laser using stimulated Brillouin scattering phase conjugation mirrors for industrial applications. Issue 6 (6th May 2013) - Kong, Hong Jin; Park, Sangwoo; Cha, Seongwoo; Kim, Jom Sool; Palashov, Oleg V.; Khazanov, Efim A.; Kravchenko, Valery B.; Fedorov, Pavel P.
Abstract A laser system that can produce 0.4 J/10 ns/10 kHz‐4 kW using a coherent beam combination with stimulated Brillouin scattering phase conjugate mirrors (SBS‐PCMs) is proposed. The 4 kW coherent beam combination laser system consists of a front‐end system, a pre‐amplifier module, a coherent beam divider/combiner, and 4 main amplifier modules. The front‐end system produces 1064 nm @ 10 kHz laser pulses, and it is amplified by the pre‐amplifier. After the pre‐amplifier module, the laser beam is divided into 4 sub‐beams. Each sub‐beam is amplified by the main amplifier module in a double‐pass configuration and reflected by SBS‐PCMs. Sub‐beams are combined by a coherent beam combiner, and the output of the total system is designed to be 4 kW. With this 4 kW laser module, high‐speed 2D holographic laser processing will be utilized. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)